Transepithelial transport of phenolic acids in Flos Lonicerae Japonicae in intestinal Caco-2 cell monolayers1. Issue 9 (2nd September 2015) - Zhou, Wei; Shan, Jinjun; Wang, Shouchuan; Cai, Baochang; Di, Liuqing
<x xml:space="preserve">Abstract</x> Intestinal absorptions of phenolic acids as well as those in Flos Lonicerae Japonicae were all mainly restricted by TJs.